Asymmetry of the Atomic Core Structure of Dissociated a‐Screw Dislocation in GaN Probed by Polarization Optical Spectroscopy. Issue 9 (24th May 2019) - Medvedev, Oleg; Albrecht, Martin; Vyvenko, Oleg
Abstract : The a‐screw dislocation related luminescence (DRL) in n‐GaN is investigated with polarization optical spectroscopy. An unusual difference in the polarization directions of two DRL spectral components is observed: directed parallel or inclined at an angle of about 40° to the dislocation line. As a tentative explanation, that property is proposed to be due to the theoretically predicted different orientations of chemical bonds in the cores of N and Ga partials of the dissociated a‐screw dislocation. Abstract : An unusual difference in the polarization directions of two spectral luminescent lines originating from a‐screw dislocations in GaN is reported: directing either parallel or inclined at an angle of about 40° to the dislocation line. A tentative explanation of that property is proposed as a result of the theoretically predicted orientations of chemical bonds in the dissociated a‐screw dislocation core.